Narratives of Black Gay Male College Students’ Experiences at Predominately White Institutions - Carmichael, Tristin Ralpheal (My University, 2018)
Under Embargo until 2028. An understanding of Black gay male college students’ lived experiences in higher education is lacking. The researcher used the critical race theory and quare theory paired together to shape the scope of this study. This study examined how Black gay male college students’ experiences affect their perception of college as social and educational environment. Further, this study illuminated how the participants made meaning of their time on campus and navigated their respective social spaces. The researcher used counter-stories and thematic analysis to capture the essence and experiences of the five participants. The findings from the in-depth, semi-structured interviews generated five themes: (a) race was not a factor in selecting choice of college, (b) I will show you who I am when I am ready, (c) they are afraid of who I am, (d) I am not your negro, and (e) I am a leader within the community. Through the quare theory and critical race theory lens, each Black gay male college student’s experience was demonstrated to be unique, but all participants experienced at least one time in their life racial discrimination and or homophobia. Furthermore, despite their harsh environments, these five participants demonstrated resilience and success during their college experience. There were three suggestions for implication of research, which include (a) a need to address LGBT organizations at PWIs that serve the gay community, (b) recruitment of Black gay males for faculty positions, and (c) faculty at PWIs need training on the sensitivity of sexual minority groups.
Chapter I: INTRODUCTION 1 | Background 1 | Purpose 3 | Statement of the Problem 4 | Significance of Study 5 | Research Questions 7 | Research Goals 7 | Conceptual Framework 9 | Quare theory 9 | Critical Race Theory 11 | Chapter II: LITERATURE REVIEW 15 | Intersectionality of Black Gay Male Identity in Higher Education 15 | Coping Strategies of Black Male College Students at PWIs 16 | Stereotypes of Black Male College Students at PWIs 18 | Racialized Experiences of Black Male College Students 20 | Perceptions Towards the LGBT Community 22 | Black Gay Males at Historically Black College and Universities 24 | Black Gay Males at PWIs 27 | Chapter III: METHODS 32 | Research Design 32 | Subjectivity Statement 34 | Participants 37 | Data Collection 38 | Data analysis 41 | Creating Counter-Stories 42 | Thematic Analysis 46 | Validity and Reliability 50 | Chapter IV: COUNTER-STORIES 52 | Introduction 52 | The Story of Rashad, the University President 52 | Background 53 | Family 59 | Racial Experience 62 | Quare Experience 72 | Coda 85 | The Story of Julius, the Nurse. 89 | Background 90 | Family 98 | Racial Experience 104 | Quare Experience 108 | Coda 112 | The Story of Roger, the Teacher 115 | Background 116 | Family 121 | Racial Experience 124 | Quare Experience 128 | Coda 134 | The Story of Blue, the Politician 135 | Background 136 | Family 145 | Racial Experience 151 | Quare Experience 153 | Coda 158 | The Story of Jimmy, the Professor 161 | Background 162 | Family 169 | Racial Experience 171 | Quare Experience 175 | Coda 181 | Chapter V: THEMATIC ANALYSIS 187 | Introduction 187 | Deciding to Attend a PWI 188 | Blue 188 | Jimmy 189 | Julius 189 | Rashad 190 | Roger 191 | Analysis of Theme 1: Race was not a factor in selecting choice of college… 191 | Coming Out 193 | Julius 194 | Jimmy 194 | Rashad 197 | Roger 200 | Blue 202 | Analysis of Theme 2: I will show you who I am when I am ready. 203 | Encountering Homophobia 206 | Rashad 206 | Julius 209 | Roger 210 | Blue 211 | Jimmy 212 | Analysis of Theme 3: They are afraid of who I am. 212 | Racial Discrimination 214 | Julius 215 | Rashad 217 | Blue 220 | Roger 220 | Jimmy 223 | Analysis of Theme 4: I am not your negro. 224 | Campus Involvement and Leadership 229 | Julius 230 | Rashad 230 | Roger 231 | Blue 232 | Jimmy 232 | Analysis of Theme 5: I am a leader within the community. 233 | Conclusion 236 | Chapter VI: DISCUSSION 238 | Summary of the Study 239 | Findings through the Quare and CRT Lens 241 | Limitations of the Study. 249 | Implications of Research 250 | Suggestions for Future Research 251 | Conclusion 252 | Epilogue 252 | REFERENCES 258 | APPENDIX A: IRB APPROVAL 265 | APPENDIX B: Recruitment Email 267 | APPENDIX C: Recruitment Flyer 269 | APPENDIX D: Audio-taped Consent statement 271 | APPENDIX E: Guided Interview Questions 273 | APPENDIX F: Final Codes 276 | APPENDIX G: Sample of Coded Passage 279 |
Keywords: Dissertations, Academic--United States; Critical Race Theory; African American gay men; African American college students; Racism; Personal narratives